2008
DOI: 10.1159/000185547
|View full text |Cite
|
Sign up to set email alerts
|

Post-conditioning Preserves Glycolytic ATP During Early Reperfusion: A survival Mechanism for the Reperfused Heart

Abstract: Background: Glycolytic activity during the transition period from anaerobic to aerobic metabolism has been demonstrated to be critical for heart recovery in isolated reperfused hearts. The purpose of this work was to investigate the relevance of the glycolytic pathway in preserving the cardiac function of post-conditioned hearts. Methods: The activation of the glycolytic pathway in post-conditioned hearts was evaluated by measuring GLUT-4 insertion, glucose consumption and lactate production. Iodoacetic acid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 29 publications
4
17
2
Order By: Relevance
“…Therefore, increased glycogen breakdown elicited by IPOC in the fed rat hearts may contribute to the increased rate of mitochondrial ATP production and ATP content, consequently accelerating functional recovery. In very broad terms, the present findings agree with those of Correa et al [21], who have reported that glucose uptake and consumption were significantly increased during the early RP phase in postconditioned rat hearts, suggesting that IPOC enhances the contribution of glucose catabolism to the total energy expenditure during reperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, increased glycogen breakdown elicited by IPOC in the fed rat hearts may contribute to the increased rate of mitochondrial ATP production and ATP content, consequently accelerating functional recovery. In very broad terms, the present findings agree with those of Correa et al [21], who have reported that glucose uptake and consumption were significantly increased during the early RP phase in postconditioned rat hearts, suggesting that IPOC enhances the contribution of glucose catabolism to the total energy expenditure during reperfusion.…”
Section: Discussionsupporting
confidence: 93%
“…In the adult heart, the subcellular localization of HK2 shifts during ischemia [47] due to the dissociation of HK2, but not HKI, from the mitochondria to cytoplasm [30, 48, 49] in response to intracellular acidification and G6P accumulation [38]. Upon reperfusion after a period of ischemia, the activity of HK is increased in both the cytosolic and mitochondrial compartments [50], probably promoted by activation of Akt signaling via the RISK pathway.…”
Section: Regulation Of Glucose Metabolism By Hk During I/rmentioning
confidence: 99%
“…Hemodynamic parameters, including left ventricular work, heart rate, contraction rate, relaxation rate, coronary flow and cardiac output, were significantly greater than those for control hearts during reperfusion, which is consistent with previous reports in similar, working (loaded) heart models (Lauzier et al, 2007; Bartkevics et al, 2016). Interestingly, MPC may also promote glucose metabolism (Correa et al, 2008) and its protective effects appear to depend on energy substrate availability (Bartkevics et al, 2016). More specifically, we previously found that the effect of MPC was dependent on the circulating energy substrate levels at reperfusion; MPC improved post-ischemic hemodynamic recovery in hearts reperfused with fatty acids and glucose, but not in hearts reperfused with glucose only (Bartkevics et al, 2016).…”
Section: Discussionmentioning
confidence: 99%